Potential Relationship between Phenotypic and Molecular Characteristics in Revealing Livestock-Associated Staphylococcus aureus in Chinese Humans without Occupational Livestock Contact - Fan, Yanping; Wang, Xiaolin; Li, Ling; Yao, Zhenjiang; Chen, Sidong; Ye, Xiaohua (Frontiers in Microbiology, 2016)
While some studies have defined Staphylococcus aureus based on its clonal complex and resistance pattern, few have explored the relations between the genetic lineages and antibiotic resistance patterns and immune evasion cluster (IEC) genes. Our aim was to investigate the potential relationship between phenotypic and molecular characteristics so as to reveal livestock-associated S. aureus in humans. The study participants were interviewed, and they provided two nasal swabs for S. aureus analysis. All S. aureus and methicillin-resistant S. aureus (MRSA) were tested for antibiotic susceptibility, multilocus sequence type and IEC genes. Of the 1162 participants, 9.3% carried S. aureus, including MRSA (1.4%) and multidrug-resistant S. aureus (MDRSA, 2.8%). The predominant multidrug-resistant pattern among MDRSA isolates was nonsusceptibility to erythromycin, clindamycin and tetracycline. The most common S. aureus genotypes were ST7, ST6, ST188 and ST59, and the predominant MRSA genotype was ST7. Notably, the livestock-associated S. aureus isolates (IEC-negative CC9, IEC-negative tetracycline-resistant CC398, and IEC-negative tetracycline-resistant CC5) were found in people with no occupational livestock contact. These findings reveal a potential relationship between S. aureus CCs and IEC genes and antibiotic resistance patterns in defining livestock-associated S. aureus in humans and support growing concern about the potential livestock-to-human transmission of livestock-associated S. aureus by non-occupational livestock contact.